Gerakan Literasi Sebagai Usaha Penguatan Kemampuan Literasi Bagi Anak Pelajar di Rumah Pintar Punggur Cerdas - Amriani Amir; Sisilya Saman Madeten; Atiqa Nur Latifah Hanum; Sahidi Sahidi; Kurniawan Kurniawan; Miftah Rahman (Journal of Community Development, 2025)
The basic literacy skills of Indonesian people are still very low compared to other countries in the world, which is a cause for concern in the world of education. The government, through the national school literacy movement, has tried hard to improve literacy skills for students, with various activities both local and national. Through formal and formal education services. The aim of this community service activity (PKM) is to strengthen literacy skills for students at the Punggur Smart Home, which is a non-formal education service, community learning activity center (PBKM) located in Punggur Kecil village, Sungai Kakap subdistrict, Kubu Raya regency. This PKM activity was attended by 25 PKBM students, using educational lecture methods and active literacy. The results of the activity evaluation showed the enthusiasm of PKBM students and their ability to respond to questions from the presenting team during the discussion activities.